A review of beam pumping energy-saving technologies - Zi-Ming Feng; Jing-Jing Tan; Qi Li; Xin Fang (Journal of Petroleum Exploration and Production Technology, 2017)
Abstract The beam pumping units applied in oilfield for more than 150 years, because it had the advantages of simple structure, reliable and durable. At present, it is still one of the most important artificial lift methods in the world. Due to the inherent structure of the beam pumping units, the balanced torque curve of gearbox has a bigger fluctuation ratio and negative torque that results low motor efficiency and load impact. Because the motor efficiency is directly proportional to the fluctuation ratio of gearbox torque, many researchers designed many types of energy-saving devices to improve the system efficiency. Therefore, based on the balance theory of gearbox torque, we introduced and discussed some significant energy-saving technologies, such as phased pumping units, dual-horsehead pumping units, shock absorber device, load reducer device, lower barbell pumping units, multi-balance device, flywheel-energy-storage device, variable speed drive device. Meanwhile, we also pointed out the future research direction.